Keterampilan Komunikasi dalam Konseling - Sukirno, Agus (Proceedings of International Conference on Da'wa and Communication, 2019)
Guidance and counseling are applied science. Guidance words and counseling words combined with simsiosis mutualism. The two words are inseparable from one another. Counselors are influential figures on the success of counseling services. One successful factor in counseling is communication skills. The Koran has explained how to communicate well, there are three stages in communicating; First, Introduction begins with greetings, shaking hands, eye contact, facial expressions, accompanied by body language. Second, Building Relationships. Realtion must be balance between conselor and conseli, so that conseli has same position with conselor. Third, closing, In this stage contain three steps, namely: conclusion, prayer, and say hello. Professional conselors are able to internalize words and actions into one integrated force. Internalization and integration of words and actions are the key for the success of counselors in implementing counseling services.